The Influence of Brand Image, Price and Quality of Service on Consumer Loyalty of the Rantauprapat Shoe Stand - Gusti Pertiwi; Yuniman Zebua; Pitriyani Pitriyani (Budapest International Research and Critics University, 2022)
This research article aims to find out the effect of brand image, price, and service quality on consumer loyalty in the rantauprapat shoe stall. The sample of this research is 80 respondents, the data obtained through the distribution of questionnaires through social media. The resulting data was tested through SPSS with regression results of brand image (0.057), price (0.071), service quality (0.115), all variables have positive influence. Significant value of brand image (0.555), price (0.701), quality of service (0.001), only service quality has a significant effect on consumer loyalty in Rantauprapat shoe stalls. With a coefficient of determination of 0.649 or 64.9% which describes the influence of variables on consumer loyalty in the rantauprapat shoe store.